Finance and Development, March 2006. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2006)
For policymakers around the world, finding ways to promote faster growth is a top priority. But what exactly do economists know and not know about growth? What direction should future research and policymaking take? This issue explores this topic, starting with a major World Bank study and research coming out of Harvard University that urges less reliance on simple formulas and the elusive search for best practices, and greater reliance on deeper economic analysis to identify each country's binding constraint(s) on growth. Other articles highlight IMF research on pinpointing effective levers for growth in developing countries and Africa's experience with growth accelerations. Also in the issue are pieces examining global economic imbalances, rapid credit growth in Eastern and Central Europe, and ways to boost productivity growth in Europe and Japan. In Straight Talk, Raghuram Rajan argues that if we want microfinance to become more than a fad, it has to follow the clear and unsentimental path of adding value and making money. Asian Development bank's Haruhiko Kuroda sets out his vision for a new financial architecture in Asia. Finally, Picture This takes an in-depth look at global employment trends.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet